9x+2y=62 4x+3y=36
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 15:34:19
9x+2y=624x+3y=369x+2y=624x+3y=369x+2y=624x+3y=369x+2y=62①4x+3y=36②由①×3-②×2得19x=114x=6将x=6代入①得9×6+2y=
9x+2y=62 4x+3y=36
9x+2y=62 4x+3y=36
9x+2y=62 4x+3y=36
9x+2y=62 ①
4x+3y=36 ②
由①×3-②×2得19x=114 x=6
将x=6代入①得9×6+2y=62 2y=8 y=4
3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2
3(x+y)-2(x-y)=11 4(x+y)+3(x-y)=9
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
9y=3x-(x-1),4(x+y)-(2x+4)=8y
根据3(x+y)-2(x-y)=11,4(x+y)+3(x-y)=9可得出x+y= ,x-y=
2(x+y)-3(x-y)=3 ,4(x+y)+3(x-y)=15
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y) x=4 y=5
(2X-3Y)(?)=-4X^+9Y^````
如果x+y/2=x-y/3=3x-2y+9/4,那么x= ,y=如果x+y/2=x-y/3=3x-2y+9/4,那么x= ,y=